Correlation of Developmental Dysplasia of Hip in Newborns with Mode of Presentation on Graf Method Ultrasound: Correlation of Developmental Dysplasia of Hip in Newborns - Marvi, Nasim; Khokhar, Samia Khalid; Alam, Omar; Qamar, Aisha; Mahar, Yasmeen; Fatimee, Sarwath (Pakistan Journal of Health Sciences, 2024)
Developmental dysplasia of hip (DDH) affects 1.5-20/1000 live births. Early detection and treatment have spared many patients from crippling. The dislocation of the hip is always postnatal. Defects in hip occur because of the flexibility of the joint capsule at birth, underdeveloped hip acetabulum and immature femur head. Objective: To correlate incidence of developmental dysplasia of hip in newborns with modes of presentation at birth (vertex, breech and transverse) using Graf method ultrasound. Methods: The six-month analytical cross-sectional study was conducted after ethical approval and informed parental consent. A total of 115 healthy newborns below 28 days age were inducted in the study. The study excluded neuromuscular disease, neural tube defects and genetic anomaly cases. The bilateral hip angles were measured on ultrasound, categorized and recorded. Modes of presentation (vertex, breech and transverse) and physical exam findings were included. Results: Hip angles were measured in 115 newborns. The vertex presentation was the most common; 96 (83.48%). Infants with vertex presentation had the significantly smaller frequency of dysplasia (p<0.001). Breech presentation had significantly high incidence of hip dysplasia (p<0.001). Bilateral pathological immature hip (2a-) and centered unstable (2c) hip dysplasia types were most common in all groups. Severe dysplasia types D and 4 were seen in the vertex and breech groups. Conclusions: Developmental dysplasia of hip occurs with vertex, transverse and breech presentation postnatally. The most frequent variants are the immature pathological and centered unstable hips. The severe forms of dysplasia occur in vertex and breech presentations